2022
DOI: 10.1017/ice.2022.126
|View full text |Cite
|
Sign up to set email alerts
|

The limits of genomic sequencing for severe acute respiratory coronavirus virus 2 (SARS-CoV-2) exposure investigations: For nosocomial outbreak reconstruction, community exposures matter, too

Abstract: charge. HCW B tested positive 2 days later. HCW B had worked daily on the renal ward 2 weeks prior to diagnosis (during the period of inpatient A's initial admission), although HCW B did not directly care for inpatient A (Fig. 1b). In total, 191 HCWs and 41 inpatients were additionally identified as having had significant close contact and were placed on enhanced surveillance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The value of HCW data can be exemplified by a study that showed that most importation events were linked to HCWs and that transmission was limited between HCWs ( 21 ). Our study also lacks community contact tracing, which was shown to be important for clarifying nosocomial transmission of SARS-CoV-2 in Singapore ( 23 ). In addition, we were unable to recover (e.g., possibly an inability to find or not stored) some (44/106, 41.5%) of the specimens for sequencing retrospectively; if we sequenced all patient and HCW COVID-positive cases from every room, we would have been able to trace the outbreak with greater resolution and likely resolve transmission chains more than the nine cases we were able to reject using lineage assignments only.…”
Section: Discussionmentioning
confidence: 99%
“…The value of HCW data can be exemplified by a study that showed that most importation events were linked to HCWs and that transmission was limited between HCWs ( 21 ). Our study also lacks community contact tracing, which was shown to be important for clarifying nosocomial transmission of SARS-CoV-2 in Singapore ( 23 ). In addition, we were unable to recover (e.g., possibly an inability to find or not stored) some (44/106, 41.5%) of the specimens for sequencing retrospectively; if we sequenced all patient and HCW COVID-positive cases from every room, we would have been able to trace the outbreak with greater resolution and likely resolve transmission chains more than the nine cases we were able to reject using lineage assignments only.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our study included periods of time with varying institutional respiratory PPE recommendations (including half of the study period when medical facemasks rather than N95 respirators were required for routine COVID-19 patient care, in part to ensure adequate N95 respiratory supply). Our study suggests that community exposures are the most common source of COVID-19 among HCP [ 21 , 22 ]. SARS-CoV-2 seropositivity has been associated with community exposures, but not with healthcare occupational exposures (ie, caring for patients with COVID-19, exposure to aerosol-generating procedures) [ 18 , 23–25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid transmission and limited pathogen evolution in early emergence of an infectious agent limit the value of WGS when not combined with epidemiologic evaluation [ 22 , 31 ]. This is especially challenging during periods of low viral diversity, such as the emergence and expansion of a new SARS-CoV-2 variant [ 32 ].…”
Section: Discussionmentioning
confidence: 99%